Nano engineering and materials technologies. IV : selected, peer reviewed papers from the 8th International Conference on Nanostructures, Nanomaterials and Nanoengineering 2016 (ICNNN 2019) and 4th International Conference on Materials Technology and Applications (ICMTA 2019), October 11-14, 2019, Kyoto, Japan - Gong, Hao (Professor of materials science); Umemura, Kazuo; Lin, Ching-Fuh; International Conference on Nanostructures, Nanomaterials and Nanoengineering 2019 : Kyoto, Japan); International Conference on Materials Technology and Applications 2019 Kyoto, Japan) (Switzerland : Trans Tech Publications Ltd, 2020)
8th International Conference on Nanostructures, Nanomaterials and Nanoengineering (ICNNN 2019) and 4th International Conference on Materials Technology and Applications (ICMTA 2019).
Calculation of Activation Energy of Commercial Grade H2O2 from DSC for Using Evaluation Thermal Hazard -- Influence of Different Preparation Methods of Silver-Modified Carbon Nitride on the Photocatalytic Activity towards Indigo Carmine Dye -- To the Question of Efficiency of Different Methods of Dispersion of Nanosecuring Suspensions -- Synthesis of Zeolite X from Bentonite via Hydrothermal Method -- Synthesis of Nanoporous Material from Lignin via Carbonization Assisted Acid Activation -- Horse Manure Derived Nitrogen-Doped Porous Carbon via Hydrothermal Carbonization for Promising Applications
Online resource; title from PDF title page (EBSCO, viewed April 8, 2020).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Nanostructured materials -- Congresses; Nanostructures -- Congresses; Nanotechnology -- Congresses; Materials science -- Congresses; Nanomatériaux -- Congrès.; Nanostructures -- Congrès.; Science des matériaux -- Congrès.; Nanotechnologie -- Congrès.; Materials science; Nanostructured materials; Nanostructures; Nanotechnology; Conference papers and proceedings